Optimum Design of Multi-Storeyed Building With Respect to Aspect Ratio - Halder, S; Maity, L, S; Sk, S; Basu, S; Roy, A; Ghosh, B.K; Majumder, S (International Journal of Computer Sciences and Engineering, 2025)
The Main Objective Of This Study Is To Investigate The Weight Of Total Required Reinforcement In A Building With Respect To Its Aspect Ratio. The Aspect Ratio Of The Building Is The Ratio Between Its Length And Breath. Thus The Main Objective Of This Project Is To Determine At Which Aspect Ratio The Steel Present In The Building Design Will Be A Cost Effective Approach. The Results Obtained For Three Building Designs Is Compared With Each Other And A Final Graph Is Plotted So That The Variation Of The Weight Of Reinforcement Can Be Clearly Distinct. So For This Reason The Reinforcements Present In The Slabs , Beams And Columns Are Being Calculated As Per The Intensity Of The Load Coming On Each Sections. So To Achieve This A Fixed Area Is Considered And All Of The Total Steel Present In The Superstructure Of The Building Is Estimated. As A Reason Of This The Aspect Ratio Of The Buildings Plays A Vital Role To Calculate The Required Weight Of Steel In The Building By Comparing It With The Aspect Ratio Graph Plotted.